BRCA Share: A Collection of Clinical BRCA Gene Variants. Issue 12 (28th September 2016) - Béroud, Christophe; Letovsky, Stanley I.; Braastad, Corey D.; Caputo, Sandrine M.; Beaudoux, Olivia; Bignon, Yves Jean; Bressac‐De Paillerets, Brigitte; Bronner, Myriam; Buell, Crystal M.; Collod‐Béroud, Gwenaëlle; Coulet, Florence; Derive, Nicolas; et al.
Abstract : BRCA ShareTM is an international alliance of academic centers and commercial testing laboratories. By integrating content of the Universal Mutation Database generated by the French Unicancer Genetic Group with the testing results of Quest Diagnostics and Laboratory Corporation of America (LabCorp), BRCA ShareTM has assembled one of the largest publicly accessible collections of BRCA variants with over 6, 200 variants currently available. In addition, to funding high quality curation, BRCA ShareTM seeks to support functional studies, targeting variants of uncertain significance. ABSTRACT: As next‐generation sequencing increases access to human genetic variation, the challenge of determining clinical significance of variants becomes ever more acute. Germline variants in the BRCA1 and BRCA2 genes can confer substantial lifetime risk of breast and ovarian cancer. Assessment of variant pathogenicity is a vital part of clinical genetic testing for these genes. A database of clinical observations of BRCA variants is a critical resource in that process. This article describes BRCA Share™, a database created by a unique international alliance of academic centers and commercial testing laboratories. By integrating the content of the Universal Mutation Database generated by the French Unicancer Genetic Group with the testing results of two large commercial laboratories, Quest Diagnostics and Laboratory Corporation of America (LabCorp), BRCA Share™ has assembled one of the largest publicly accessible collections of BRCA variants currently available. Although access is available to academic researchers without charge, commercial participants in the project are required to pay a support fee and contribute their data. The fees fund the ongoing curation effort, as well as planned experiments to functionally characterize variants of uncertain significance. BRCA Share™ databases can therefore be considered as models of successful data sharing between private companies and the academic world.